PERAN POLA ASUH AUTORITATIF DAN KECERDASAN EMOSIONAL TERHADAP DISIPLIN DIRI SISWA KELAS XI IPA SMA SANTO YOSEPH DENPASAR - Aitama, Yolanda Budi; Rustika, I Made (Jurnal Psikologi Udayana, 2016)
Self discipline is important for students. Students who have high self discipline will take action based on social norms or rules that have been created. Self discipline is influenced by external factors and internal factors. Authoritative parenting style is one of external factors that influence to change of behavior, while one of internal factors can be drive human behavior is emotional intelligence. This study aims to determine whether there is the role of authoritative parenting style and emotional intelligence to self discipline students. Subjects in this study were student of senior high school grade XI science at Santo Yoseph Denpasar. Instruments in this study is authoritative parenting scale, emotional intelligence scale, and self discipline scale. The results of this study showed a regression coefficient (R) of 0.507 (F=29.538,P<0.05), this means that authoritative parenting style and emotional intelligence contribute to self discipline. The coefficient of determination (R2) of 0.325, which means that the authoritative parenting style and emotional intelligence have effective contribution of 32.5% to self discipline. Emotional intelligence have standardized beta coefficient of 0.508 (P<0.05) and authoritative parenting style have standardized beta coefficient of 0.196 (P<0.05). Emotional intelligence have more contribute than authoritative parenting style to self discipline.Keywords : Authoritative Parenting Style, Emotional Intelligence, Self Discipline